Intimate Relations: Molecular and Immunologic Interactions Between Neisseria gonorrhoeae and HIV-1 - Guvenc, Furkan; Kaul, Rupert; Gray-Owen, Scott D. (Frontiers in Microbiology, 2020)
While the global incidence of human immunodeficiency virus (HIV-1) remains well above UNAIDS targets, sexual transmission HIV is surprisingly inefficient. A variety of host, viral and environmental factors can either increase HIV-1 shedding in the infected partner and/or increase mucosal susceptibility of the HIV-1 uninfected partner. Clinical and epidemiological studies have clearly established that Neisseria gonorrhoeae substantially enhances HIV-1 transmission, despite it not being an ulcerative infection. This review will consider findings from molecular, immunologic and clinical studies that have focused on each of these two human-restricted pathogens, in order to develop an integrative model that describes how gonococci can both increase mucosal shedding of HIV-1 from a co-infected person and facilitate virus establishment in a susceptible host.